Area Deprivation Index and Cardiovascular Events: CAN CARDIAC REHABILITATION MITIGATE THE EFFECTS?. Issue 5 (19th September 2021) - Guhl, Emily N.; Zhu, Jianhui; Johnson, Amber; Essien, Utibe; Thoma, Floyd; Mulukutla, Suresh R.; Magnani, Jared W.
Abstract : Supplemental Digital Content is Available in the Text. This study evaluated the association of Area Deprivation Index (ADI), a marker of neighborhood social composition, with risk of recurrent cardiovascular outcomes and assessed the modifying effect of CR. Our findings showed that although increased ADI was adversely associated with rehospitalizations and mortality, individuals with CR had significantly improved outcomes. Abstract : Introduction: Neighborhood socioeconomic status is associated with health outcomes. Cardiac rehabilitation (CR) provides a cost-effective, multidisciplinary approach to improve outcomes in cardiovascular disease. We aimed to evaluate the association of the Area Deprivation Index (ADI), a marker of neighborhood social composition, with risk of recurrent cardiovascular outcomes and assessed the modifying effect of CR. Methods: We identified patients with a primary diagnosis of (1) myocardial infarction or (2) incident heart failure (HF) admitted to a large-sized regional health center during 2010-2018. We derived the ADI from home addresses and categorized it into quartiles (higher quartiles indicating increased deprivation). We obtained number of CR visits and covariates from the health record. We compared rehospitalization (cardiovascular, acute coronary syndrome [ACS], and HF) and mortality rates across ADI quartiles. Results: We included 6957 patients (age 69.2 ± 13.4 yr, 38% women, 89% White race). After covariate adjustment, the ADI was significantly associated with higher incidence rates (IRs)/100 person-yr of cardiovascular rehospitalization (quartile 1, IR 34.6 [95% CI, 31.2-38.2]; quartile 4, 41.5 [95% CI, 39.1-44.1], P < .001). In addition, the ADI was significantly associated with higher rates of rehospitalization for HF ( P < .001), ACS ( P < .012), and all-cause mortality ( P < .04). These differences in rehospitalization and mortality rates by the ADI were no longer significant in those who attended CR. Conclusions: We found the increased ADI was adversely associated with rehospitalizations and mortality. However, in individuals with CR, outcomes were significantly improved compared with those with no CR. Our findings suggest that CR participation has the potential to improve outcomes in disadvantaged neighborhoods.